Improving the social cognitive deficits of schizophrenia: a community trial of Social Cognition and Interaction Training (SCIT). (August 2013) - Parker, Stephen; Foley, Sharon; Walker, Philippa; Dark, Frances
Objective: Social Cognition and Interaction Training (SCIT) is a Cognitive and Behavioural Therapy (CBT) informed group therapy with an emerging evidence base in addressing the social cognitive deficits associated with schizophrenia. This paper evaluates the application of this therapy within a community public mental health setting in Australia. Method: A mixed methods approach to the evaluation was undertaken, including survey data and thematic analysis. Results: Considerable challenges were met in the trial of SCIT in this 'real-world' setting. The qualitative data suggested that at least a subset of participants viewed the program as valuable and relevant to their needs. Conclusions: Further research is required to realise the benefits of SCIT found in research settings, in the real world of public community psychiatric practice.